PENGARUH STRUKTUR MODAL, AKTIVITAS DAN EFISIENSI MODAL KERJA TERHADAP PROFITABILITAS SEKTOR INFRASTRUKTUR, UTILITAS DAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Puti Ayu Sriwananda -; Emianti Situmorang -; Puja Madwi -; Yenni Aprilia Sari -; Januardin - (JEBIM Prima, 2021)
The object of this study was to analyze the effect of Capital Structure, Activities and Working Capital Efficiency on the Profitability of the Infrastructure, Utilities and Transportation sectors in the Indonesia Stock Exchange for the 2014-2018 Period. This research was conducted on 79 companies. There are 19 samples with purposive sampling technique. From the results of the analysis. known phenomena at PT. Samudera Indonesia total debt in 2014-2015 has decreased but net income has also decreased. In the State Gas Company (Persero), total assets in 2014-2015 experienced an increase but their net income decreased. And in the Indonesian telecommunications company sales in 2017-2018 have increased but their net profit has decreased. This phenomenon is not in accordance with the prevailing theory. The method for testing classical assumptions is Multiple Linear Regression Analysis. The results of the simultaneous study of Capital Structure, Activities and Working Capital Efficiency together have a significant positive effect on profitability. Partially, the Capital Structure and Activities have a significant positive effect on profitability, while the efficiency of working capital has a significant negative effect on profitability. Based on the results of the analysis it is suggested that companies maintain the Capital Structure and Activities of the company and be more efficient in managing Working Capital.